PENINGKATAN HASIL BELAJAR LOMPAT TINGGI MENGGUNAKAN MODIFIKAS PERMAINAN LOMPAT KARET PADA SISWA TUNARUNGU DI SDLB NEGERI SEMARANG TAHUN AJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine whether modifications rubber jump games can improve learning outcomes of students with hearing impairment in learning the high jump at SDLB Semarang. The implementation consists of two cycles. Each held one meeting cycle consists of four stages, namely: planning, implementation, observation, and reflection. The subjects of this study were fourth grade deaf students Semarang SDLB of 10 people consisting of 8 male students and 2 female students. The instruments used in this study were the test performance of students, student observation sheet, and a written test. Based on the results, the percentage of mastery learning in the first cycle, 10 % aspects of psychomotor, affective aspects of 40 %, 40 % cognitive, and mastery learning students in the classical 30 % of the number of students. In the second cycle psychomotor aspects 80 %, 90 % affective aspects, cognitive aspects of 100 %, and completeness of student learning in the classical 90 % of the number of students. In the present study showed an increase in the classical mastery learning students by 60 %, from the first cycle 30% to 90 % in the second cycle.